Chobani's oat expansion : marketing in the emerging oat beverage category in the United States - Osland, Asbjørn, (SAGE Business. Cases., 2022)
Chobani developed a dominant presence as a Greek yogurt maker, but decided to expand beyond dairy options in 2017 with a move into coconut-based yogurts and later into oat-based products. The company's CEO, Ulukaya, wanted to diversify to protect the firm against a downturn in dairy products. Growing from that philosophy, Chobani introduced oat products to the U.S. market in 2019. Sherdonna Williams, the product manager for the company's oat products, is examining how to compete against other oat- and plant-based beverages in the United States. Sherdonna's dilemma is identifying how to target key market segments and developing a strategy to compete against leading oat brands. Oat products offer less protein than dairy and more added sugar but some consumers have an aversion to dairy due to lactose intolerance or concerns about global warming or animal rights. Chobani tries to appeal to varied segments.